THE BNCC: THE CLASH BETWEEN DIGITAL EDUCATION AND THE PROMOTION OF CRITICAL THINKING IN ITS POSSIBLE INTERFACES - Lima, Getúlio de Souza [UNESP]; Lastória, Luiz Antônio Calmon Nabuco [UNESP] (Revista Pesquisa Qualitativa - RPQ, 2024)
This article is the result of a research about medial process of social spectacularizing accentuated by the advent of the “digital culture” nowadays driven by the “platform capitalism”. Its goal is to expose some educational implications arising from the pedagogical rearrangements in the face of the strengthening algorithmic insertions in teaching programs to standardize the conduct of teachers, as provided for in the National Common Curricular Base (NCCB). We analyzed some social and educational consequences of computational thinking through the software trend in the ongoing reform of basic education. The results showed that digital priority through the didactic dirigisme undermines the development of critical thinking in the face of algorithmic coldness.
A BNCC: O EMBATE ENTRE A EDUCAÇÃO DIGITAL E A PROMOÇÃO DO PENSAMENTO CRÍTICO EM SUAS POSSÍVEIS INTERFACES
Keywords: Algorithmization; Didatic dirigism; Education and digital culture